Buthionine sulfoximine, a glutathione depletor, attenuates endotoxic fever and reduces IL-1β and IL-6 level in rats. (February 2017) - Wrotek, Sylwia; Domagalski, Krzysztof; Jędrzejewski, Tomasz; Dec, Eliza; Kozak, Wiesław
Highlights: Buthionine sulfoximine (BSO) decreases spleen glutathione level. BSO inhibits endotoxic fever. BSO attenuates expression of LPS-stimulated IL-1β and IL-6 genes. BSO decreases plasma level of IL-1β and IL-6. Abstract: Purpose: The aim of our study was to investigate the effect of buthionine sulfoximine (BSO) - a glutathione depletor - on a course of endotoxic fever and IL-1β and IL-6 production. Material and methods: Male Wistar rats were subjected to intraperitoneal injection of lipopolysaccharide (LPS) from E . coli (50 μg/kg, ip ) to provoke fever. The level of spleen glutathione, plasma interleukin (IL)-1β, IL-6, and deep body temperature (Tb) were measured. Results: The LPS administration provoked fever (the average Tb was 38.14 ± 0.05 °C in NaCl/LPS-treated rats vs 37.10 ± 0.03 °C in control, not-treated rats; p < 0.001). We observed that LPS injection induced a decrease in spleen glutathione level (7.67 ± 0.92 nM/g vs 13.27 ± 0.47 nM/g in not-treated rats; p < 0.001). Furthermore, the injection of LPS provoked an elevation of plasma IL-1β and IL-6 concentration (from values below the lowest detectable standard in not-treated animals to 199.99 ± 34.89 pg/mL and 7500 ± 542.21 pg/mL, respectively; p < 0.001). Pretreatment with BSO enhanced glutathione decrease in LPS-treated rats (5.05 ± 0.49 nM/g), and significantly affected fever (maximal Tb was 37.81 ± 0.07°C in BSO/LPS-treated rats vs 38.76 ± 0.11 °C in NaCl/LPS-treated rats). BSO 4 h after LPS injection decreased IL-1β and IL-6 gene expression (about 1.5 fold, and 2 fold, respectively). In a consequence we observed a decrease in plasma IL-6 concentration (4 h after LPS injection plasma IL-6 was 4167.17 ± 956.54 pg/mL in BSO/LPS-treated rats vs 7500 ± 542.21 pg/mL in NaCl/LPS-treated rats; p < 0.001), and later IL-1β (7 h after LPS injection the IL-1β concentration was not detected). Conclusion: Based on these data, we conclude that BSO, in addition to well-known application as an inhibitor of glutathione synthesis, is an antipyretic agent which reduces both IL-1β and IL-6 concentration.